Biological, Physical, Ergonomic, Chemical and Psychological Hazard Awareness among Health care and Non-Healthcare Workers - Hisam, Aliya; Mashhadi, Syed Fawad; Saqib, Arsalan; Naveed, Muhammad Saad; Sadiq, Muhammad Rehan; Imtiaz, Touseef; Ashraf, Arslan (Pakistan Armed Forces Medical Journal, 2024)
Objective: To assess the level of awareness regarding various hazards among healthcare and non-healthcare workers. Study Design: Analytical cross-sectional study. Place and Duration of Study: Conducted in Rawalpindi over a 6-month duration from Nov 2021 to Apr 2022. Methodology: The estimated sample size was 228. Sampling technique was non-probability convenient sampling. Healthcare group included individuals from medical field. Non healthcare group included persons from other fields. Non willing persons were excluded. A preformed questionnaire with some changes was used. Data was collected through Google forms and analyzed in SPSS version 26. Results: The sample included 162 males and 66 females. Mean age was 21.10±2.76. Out of the total, 75.9% fell into healthcare group while 24.1% landed into Non healthcare group. In Healthcare group highest awareness was about contact with contaminated specimens among Biological hazards (78.6%), Radiations among Physical hazards (76.9%), standing for prolonged periods among Ergonomic hazards (69.9%), corrosives among Chemical hazards (74.0%), and stress among Psychosocial hazards (86.7%). In Non healthcare group highest percentages were of injuries among Biological hazards (72.7%), poor ventilation among Physical hazards (67.3%), standing for prolonged periods among Ergonomic hazards (70.9%) and stress among Psychosocial hazards (80%). Conclusions: The study showed that for most of the hazards assessed the Healthcare workers are relatively more aware as compared to the Non healthcare group.